PARADOKS DESENTRALISASI DAN KESEJAHTERAAN : Kalimantan Timur Kaya Tapi Miskin - Ali Hapsah, Muhammad; Mas?udi, Wawan (Jurnal Desentralisasi, 2012)
East Kalimantan is a province full of paradox. This region has considerable economic potential measured in terms of its abundant endowments of natural resources, including oil, natural gas, gold, coal and forestry. Yet, East Kalimantan still lacks infrastructure, has poor human resources and high levels of unemployment, factors which condemn much of the population to a life of poverty and hardship. The new system of regional autonomy, which has been implemented since 2001, was expected to give more benefit to the regions, as regional governments have held relatively more power and fiscal capacity. Law 22/1999, which has been revised twice, has provided more authority to regional governments to manage their respective regions. The introduction of fiscal decentralisation through Law 25/1999, further revised in Law 33/2004, has favoured regions rich in natural resources such as East Kalimantan. As it has abundant natural resources, this region has received greatly increased funds from the central government due to the implementation of sharing revenue formulagenerated from the exploitation of natural resources. These supposed to give more opportunity for the rich regions such East Kalimantan to accelerate regionaldevelopment and bring their people to greater prosperity. Nevertheless, East Kalimantan has realized neither the objectives of regional autonomy nor thecommunity aspirations for a more prosperous society. This paper aims to examine the extent to which the regional autonomy laws have impacted on people welfare in East Kalimantan.